Effect of total charge on the electronic structure of thiolate-protected X@Ag12 superatoms (X = Ag, Au). Issue 8 (17th January 2023) - Nakamura, Katsunosuke; Ito, Shun; Koyasu, Kiichirou; Tsukuda, Tatsuya
Abstract : Gas-phase photoelectron spectroscopy revealed that the highest occupied molecular orbital of the icosahedral X@Ag12 core (X = Ag or Au) was destabilized by ~3.7 eV by the increased total negative charge from –1 to –3 due to the ligand layers. Abstract : Electronic structures of chemically synthesized silver-based clusters [XAg16 (TBBT)12 ] 3− (X = Ag or Au; TBBT = 4- tert -butylbenzenethiolate) having an icosahedral X@Ag12 superatomic core were studied by gas-phase photoelectron spectroscopy and density functional theory calculations. The electron binding energy of the highest occupied molecular orbital (HOMO) with a 1P superatomic nature was determined to be 0.23 and 0.29 eV for X = Ag or Au, respectively. Resonant tunnelling electron emission through the repulsive Coulomb barrier (RCB) was observed. From the kinetic energy of the tunnelling electrons, it was estimated that the lowest unoccupied molecular orbital (LUMO) was supported at 1.51 and 1.62 eV above the vacuum level by the RCB for X = Ag or Au, respectively. The HOMO of [XAg16 (TBBT)12 ] 3− (X = Ag or Au) was destabilized by 3.74 and 3.71 eV, respectively, compared with those of [XAg24 (DMBT)18 ] − (DMBT = 2, 4-dimethylbenzenethiolate) having the icosahedral X@Ag12 core due to the larger negative charge imparted by the ligand layers.